Palynological origin, chemical composition, lipid peroxidation and fatty acid profile of organic Tuscanian bee-pollen. Issue 2 (15th March 2017) - Sagona, Simona; Pozzo, Luisa; Peiretti, Pier Giorgio; Biondi, Cesare; Giusti, Matteo; Gabriele, Morena; Pucci, Laura; Felicioli, Antonio
Abstract : The aim of this work is to characterize fresh bee-pollen in order to define the main nutritional properties of this apiary product for future legislation. Organic bee-pollen ( n = 5) harvested from Lucca (Tuscany, Italy) was studied for palynological analysis, nutritional content (dry matter, crude protein, lipid, ash and carbohydrate contents), thiobarbituric acid reactive substances (TBARS) content and fatty acids (FA) profile. The chemical composition analyses showed an average of 849 g/kg for dry matter, 253 g/kg for proteins, 12.9 g/kg for lipids, 24.7 g/kg for ash, and 561 g/kg for carbohydrates. The average value of TBARS content was 0.96 mg malondialdehyde/kg. Concerning FA composition, results showed differences among organic Tuscanian bee-pollen species. All the investigated pollen species had linoleic acid with a mean value of 55.4 g/kg of total FAs and, α-linolenic acid, with a mean value of 147 g/kg of total FAs. An average n-6/n-3 polyunsaturated fatty acid (n-6/n-3 PUFA) ratio of 1.70 was found. Considering that the n-6/n-3 PUFA ratio and linoleic acid/α-linolenic acid ratio are considered important for the prevention of human diseases, the Tuscanian organic bee-pollen may be of nutraceutical relevance.